2017
DOI: 10.3390/nu9050506
|View full text |Cite
|
Sign up to set email alerts
|

Fat, Sugar, and Bone Health: A Complex Relationship

Abstract: With people aging, osteoporosis is expected to increase notably. Nutritional status is a relatively easily-modified risk factor, associated with many chronic diseases, and is involved in obesity, diabetes, and coronary heart disease (CHD), along with osteoporosis. Nutrients, such as fats, sugars, and proteins, play a primary function in bone metabolism and maintaining bone health. In Western nations, diets are generally high in saturated fats, however, currently, the nutritional patterns dominating in China co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 71 publications
(110 reference statements)
1
50
2
3
Order By: Relevance
“…Several studies have shown that high fat or high glycemic load diets are associated with decreased bone mineral density; as bone strength diminishes, adverse microstructure and inflammatory changes occur in the cancellous bone compartment, which is involved in both lipid metabolism and the bone marrow microenvironment [90]. In obesity, GLP-1 and other protective gut molecules decrease and the process of osteopenia and/or osteoporosis intensifies progression to osteosarcopenia [91].…”
Section: Osteosarcopenic Obesitymentioning
confidence: 99%
“…Several studies have shown that high fat or high glycemic load diets are associated with decreased bone mineral density; as bone strength diminishes, adverse microstructure and inflammatory changes occur in the cancellous bone compartment, which is involved in both lipid metabolism and the bone marrow microenvironment [90]. In obesity, GLP-1 and other protective gut molecules decrease and the process of osteopenia and/or osteoporosis intensifies progression to osteosarcopenia [91].…”
Section: Osteosarcopenic Obesitymentioning
confidence: 99%
“…13 modules with more than 0.99 R square (sTab4, Fig4A) are obtained by the model and plotted in rank by their importance (Fig4B, sTab4). In addition, for the correlation with clinical indexes, the negatively correlated modules like the lactate consumption, sucrose degradation that would impart a significant impact on bone structural integrity [24] and tryptophan degradation which plays a complicated role in osteoblastic differentiation [25] are positively associated with HDL and CROSSL, but negatively with TG. By comparison, the BMD positive modules, for example the pectin degradation that would inhibit bone resorption and strength the bone [26], trehalose degradation which could be effective on the prevention of bone mass loss [27], arginine degradation that can prevent bone mass loss and bone collagen breakdown in rats' model [28], mucin degradation and rhamnose degradation.…”
Section: Results 4 Modules Suggesting For Bone Mass Lossmentioning
confidence: 99%
“…Some targeted modules, like the degradation of pectin [26], trehalose [27] and arginine [28], are related to bone protection. But for the sucrose degradation module, it would impart a significant impact on bone structural integrity [24], which suggest that we should reduce the intake of foods rich in sucrose in our daily diet.…”
Section: Discussionmentioning
confidence: 99%
“…However, such differences would have been reflected into subcutaneous adipose tissues and muscle, which is not the case in our study. [38][39][40] Finally, while promising, for this approach to become more widely used as a research or clinical tool, the CSE and analysis method should be validated at other skeletal sites (eg, vertebral bodies) and within other regions of interest.…”
Section: Discussionmentioning
confidence: 99%